Actual status of development and application of internet of things in Vietnam - Sinh, Bach Tan; Hoa, Dang Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
The paper introduces the basic notions of the eco system of Internet of Things (IoT) with 4 main components (hardware, software/connections, services and institutions/policies) and the eco system of the commercial IoT with two groups of actors (providers of service/application including providers of equipment, networks and platforms, and clients). Then, a global picture is drawn for development and application of IoT in Vietnam with the main actors involved into the IoT and some initial results of application of IoT in sectors of urban development, transport, agriculture and smart homes. The paper offers some recommendations for promotion of process of development and application of IoT in Vietnam. Code: 18100501